Comportamiento de durazneros y nectarinos precoces en la IV region de Chile - Muñoz S, C.=700 1 Sepulveda R, G.; Ibacache G, A.; Valenzuela B, J.; Sherman, W.B.
(En, Es)
Ilus., 6 ref.
Keywords: DURAZNO; NECTARINA; ADAPTACION; PRODUCCION POTENCIAL; CHILE; AGRICULTURA TECNICA